Measurement of gravitational acceleration with the leak tank method - Reliusman Dachi; Ikhsan Setiawan (Journal of Physics: Theories and Applications, 2018)
An experimental device of the mechanics of tank draining under gravity has been constructed. It mainly consists of a cylindrical tank with a circular orifice at the center bottom of the tank. The inner radius of the tank is 134 mm, while there are seven variations of orifice radius, those are 2.25 mm, 2.50 mm, 3.00 mm, 3.50 mm, 4.00 mm, 5.00 mm, and 6.00 mm. The tank is filled by water which is then allowed to flow out throuh the orifice. This experiment can be used to measure the value of gravitational acceleration () on the experiment location. We call this method as the leak tank method.  The measurement of g is carried out by measuring the total time to drain the tank from 300 mm initial height of water surface inside the tank for various orifice radius. It is found in this experiment that  = (9.89± 0.03) m/s2. This result is good enough because it is almost the same as the conventional standar value of 9.80665 m/s2 with discrepancy of around 0.85%. It indicates that the leak tank method which is described in this paper can be used to estimate the gravitational acceleration value with a good result.